DIFFERENCES IN INDICATORS OF SITUATIONAL EFFECTIVENESS BETWEEN TEAMS THAT COMPETE IN DIFFERENT COMPETITIONS RANKS - Alen Kapidžić; Edin Mujanović; Amra Nožinović-Mujanović; Adnan Salkić; Elvedin Mejremić (Sport Scientific And Practical Aspects, 2025)
The main goal of this study is to identify the differences in some variables of situational effectiveness for the national soccer teams participating at the Euro 2008 Soccer Championship and the teams that took part in the BiH (Bosnia and Herzegovina) Premier League season 2008/2009. The obtained results indicate that the Premier League team had organized a larger number of attacks per game. Also on this level of competition the team had more shots blocked inside the penalty area and a larger number of shots defended by the goalkeeper. It tells us that the Premier League teams are technically inferior, and do not have rational tactical procedures at the stage of defense in relation to the participants of the European Soccer Championship. Also, we can see that the effective duration of games in the Premier League is shorter in relation to the European Championships because at this level of competition teams have more interruptions during the game. The results show that the BiH Premier League teams should improve all technical – tactical procedures, with emphasis on bigger situational variability, and work on rationalization of the tactical procedures within individual and group tactics in both, offense and defence, in order to increase the level of technical preparedness of the players to create conditions for more efficient final and finding of adequate responses for unforeseen situations.